SIFAT FISIS MEKANIS BAMBU LAPIS SEBAGAI BAHAN BAKU PRODUK INTERIOR - Arhamsyah, Arhamsyah (Kementerian Perindustrian, 2011)
Research on the utilization of bamboo as a raw material layer interior products have been made. This research aims to determine the nature of plybamboo in terms of technical aspects / processes of manufacture, physical and mechanical, the influence of weight variation labur adhesive, adhesive types and kinds of bamboo products plybamboo.This type of bamboo used is sweet bamboo (Gigantochloa atter Kurz) and bamboo lear (Gigantochloa apus Kurz).The adhesive used was adhesive Polyvinil Acetat (PVAc) and Chloroprene with adhesive labur weight each - each 150 gr/m2, 200 gr/m2 and 250 gr/m2. The parameters tested were water content, density, flexural strength of dry and delamination.The results showed that the treatment using bamboo material with adhesive Chloroprene sweet heavy labur 250 gr/m2 produce the best plybamboo.Keywords: bamboo, glue, physical, mechanical